PENGARUH KETIMPANGAN GENDER TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (34 PROVINSI) TAHUN 2015-2020 - Leonard Deris (Jurnal Pendidikan Ekonomi Indonesia, 2022)
The purpose of this study is to gain an understanding of (1) Analyzing the influence of gender inequality from the Ratio of Life Expectany on economic growth in Indonesia, (2). Analyzing the influence of gender inequality from Ratio Mean Years School on economic growth in Indonesia, (3) Analyzing the influence of gender inequality from the Ratio of Labor Force Participation on economic growth in Indonesia. This research uses secondary data with documentation method and library study method. This research method is descriptive with quanitative approach. The estimation model uses panel data regression, Fixed Effect Robust Model. From the results of the research that has been done, it was obtained that the variable Female/Male Ratio of Life Expectancy insignificant influence on economic growth. Female/Male Ratio of Mean Years School has a positive significant influence on economic growth. Female/Male Ratio of Labor Force Participation variables has a positif significant influence on economic growth